Non-visual arrestins function as simple scaffolds assembling the MKK4–JNK3a2 signaling complex - Zhan, Xuanzhi (2011)
Arrestins are a small family of proteins with four mammalian members that play key roles in the regulation of multiple GPCR-dependent and -independent signaling pathways. Although arrestins were reported to serve as scaffolds for MAP kinase cascades, promoting the activation of JNK3, ERK1/2, and p38, the molecular mechanisms involved were not elucidated and even the direct binding of arrestins with MAP kinases were never demonstrated. Here using purified proteins we show that both non-visual arrestins directly bind JNK3α2 and its upstream activator MKK4, and that the affinity of arrestin-3 for these kinases is higher than that of arrestin-2. Reconstitution of the MKK4-JNK3α2 signaling module from pure proteins in the presence of different arrestin-3 concentrations showed that arrestin-3 acts as a “true” scaffold, facilitating JNK3α2 phosphorylation by bringing the two kinases together. Both JNK3α2 phosphorylation by MKK4 and JNK3α2 activity towards its substrate ATF2 increase at low and then decrease at high arrestin-3 levels, yielding bell-shaped concentration dependence expected with true scaffolds that do not activate the upstream kinase or its substrate. Thus, direct binding of both kinases and true scaffolding is the molecular mechanism of arrestin-3 action on the MKK4-JNK3α2 signaling module.